PENINGKATAN HASIL DAN AKTIVITAS BELAJAR PESERTA DIDIK PADA MUATAN PEMBELAJARAN MATEMATIKA MATERI VOLUME BANGUN RUANG DENGAN MODEL DISCOVERY LEARNING METODE PEMBERIAN TUGAS DI KELAS VI SD N 07SARILAMAK - DAHRIAL DAHRIAL (JURNAL ILMIAH SIMANTEK, 2023)
This study aims to see and analyze the use of the Discovery Learning Model of the Task Giving Method to improve the Activities and Learning Outcomes of Students in Mathematics Learning Content on the Volume of Spaces in Class VI Odd Semester of SDN 07 Sarilamak for the 2020/2021 Academic Year. This research was conducted using the Classroom Action Research method which consists of two cycles, where each cycle consists of; planning, action, observation and reflection. It was carried out from August to October 2021. The results obtained from this study are that by using a scientific approach, the discovery learning model, the method of giving assignments can improve students' learning activities and results. This is evident from the increase in student learning completeness in each cycle, pre-cycle student learning activities are 61%, in cycle I 78% and cycle II 95%. For pre-cycle teacher activities 50%, cycle I 57% and increased in cycle II to 85% and for pre-cycle knowledge learning outcomes 67.07 = 40%, cycle I 73.35 = 54%, and cycle II 85.89 = 93%. For the learning completeness of skills, namely pre-cycle 66.82 = 43%, cycle I 73.84 = 62%, and cycle II 84.64 = 89%.The conclusion obtained from this research is that the use of a scientific approach discovery learning model method of giving assignments can improve the activities and learning outcomes of students.